Difficult situations in relationships with parents based on the examples of biographies of outstanding individuals of Polish science and culture - Bernasiewicz, Maciej (Difficult situation in biographies: Volume 9, 2025)
Biographical analyzes conducted by the author in the years 2020–2023 based on scientific and literary monographs devoted to outstanding figures of Polish science and culture allowed for insight into their childhood and early adulthood. In the generational families of such figures as Joseph Conrad-Korzeniowski, Wojciech Kilar, Ignacy Paderewski, Ryszard Kapuściński, Stanisław Lem, Władysław Reymont, Józef Tischner, Henryk Sienkiewicz, Janusz Korczak, Bronisław Malinowski, Czesław Miłosz, and Zygmunt Bauman, the presence of an upbringing environment was found that it favored the maturation of great talents. However, there were many difficult situations in the relationships of the mentioned individuals with their parents. The text qualitatively characterizes these situations, which are classified into three categories of phenomena: „confrontation with parents’ ambitions”, „embitterment with the parent’s attitude to life” and „political disputes”.